Biphasic Enantioselective Fluorescent Recognition of Amino Acids by a Fluorophilic Probe. Issue 33 (25th April 2019) - Zhu, Yuan‐Yuan; Wu, Xue‐Dan; Abed, Mehdi; Gu, Shuang‐Xi; Pu, Lin
Abstract: A fluorophilic fluorescent probe based on a perfluoroalkyl‐substituted bis(binaphthyl) compound was designed and synthesized. It displayed a highly enantioselective fluorescence response toward structurally diverse amino acids in a biphasic fluorous/aqueous system with enantiomeric fluorescent enhancement ratio ( ef ; Δ I D /Δ I L ) values up to 45.2 (histidine). It can be used to determine the enantiomeric compositions of amino acids and also allows the amino acid enantiomers to be visually discriminated. NMR and mass‐spectroscopic investigations provided insights into the observed high enantioselectivity. This biphasic fluorescent recognition was used to determine the enantiomeric composition of the crude phenylalanine products generated by an enzyme‐catalyzed asymmetric hydrolysis under various reaction conditions. The fluorous‐phase‐based fluorescence measurement under the biphasic conditions was able to minimize the interference of other reaction components and thus has potential in asymmetric reaction screening. Abstract : Enantioselective : A fluorophilic fluorescent probe based on a perfluoroalkyl‐substituted bis(binaphthyl) compound was designed and synthesized. It shows a highly enantioselective fluorescence response toward structurally diverse amino acids in a biphasic fluorous/aqueous system (see figure) and can be used to determine the amino acid enantiomeric compositions as well as their enantiomers.